REACTIVE OXYGEN SPECIES ACCUMULATIONS, PHENYLALANINE AMMONIA-LYASE ACTIVITY AND PHENOLIC ACID COMPOSITION OF SOYBEAN [GLYCINE MAX(L.) MERR.] CV. GROBOGAN THAT EXPOSED TO MULTIPLE STRESS OF PURPLE NUTSEDGE (CYPERUS ROTUNDUS L.) INTERFERENCE AND DROUGHT - S. Darmanti; Santosa; L. H. Nugroho; K. Dewi (Journal of Animal and Plant Sciences, 2018)
Plants respond to environment stresses in various ways, namely by Reactive Oxygen Species synthesizing in abundance that can trigger the activation of the antioxidant defense system and increase of Phenylalanine Ammonia-lyase enzyme activity that catalyses secondary metabolites formation such as phenolic compounds. Phenol can act as an antioxidant and as allelochemicals which can inhibit plant competitors growth in the surrounding vegetation. This research was carried out using Completely Randomized Designs (CRD) with two factor, i.e. purple nutsedge interference (control, three and six purple nutsedge) and drought (control, mild and severe). The aims of the research was to assess the effect of the multiple stresses of purple nutsedge interference and drought against ROS accumulation in the form of O2.-and H2O2, PAL activity and phenolic compounds composition. The results showed that purple nutsedge interference and drought  interact in determining the increase of ROS accumulation, PAL activity and accumulation of phenolic compounds in the leaves of soybean, but the composition of phenolic compounds showed increased accumulation occurs in vanillic acid, 2,5-dihydroxybenzoic acid, caffeic acid, syringic acid,  trans-cinnamic acid and salicylic acid, while the composition of 4-hydroxybenzoic acid, trans-ferulic acid and  coumaric acid show variation in different treatments.
Keywords: darmantisri@yahoo.co.id